Cause of fevers and diagnostic strategies among the HIV patients hospitalized in the regional hospital of Comè (Southern Benin): A national study - AGBODANDE, KOUESSI ANTHELME; ATTINSOUNON, COSSI ANGELO; WANVOEGBE, FINANGNON ARMAND; AZON KOUANOU, ANGÈLE; KPOSSOU, ABOUDOU RAÏMI; ZANNOU, DJIMON MARCEL; HOUNGBE, FABIEN (My University, 2015)
Over the past decade, considerable progress has been achieved in expanding the access towards antiretroviral therapy (ART) in developing countries against AIDS, however Sub-Saharan Africa continues to record the highest number of deaths related to HIV. A cross-sectional, descriptive and analytical study was conducted in the department of polyvalent medicine of the first referral hospital of Comè over a two-year-period, from 1st January 2012 to 31st December 2013 to determine the cause of fever among the HIV patients. A total of 87 HIV infected patients were hospitalized during the study period. Among them, there were 60 cases of fever (69.0%). The mean age was 39.4 ± 11.3 years old and the sex ratio (M / F) was 0.94. Acute fever was recorded in 41.7% of cases and long term fever in 58.3% of cases. Infectious diseases like diarrhoea, pneumonia, oropharyngeal candidiasis, tuberculosis and cerebral toxoplasmosis were the main causes of fever in hospitalized HIV patients (96.3%).
Keywords: HIV; fever; AIDS; ART; Immune deficiency diseases; Benin